Type IV collagens regulate BMP signalling in Drosophila - Wang, Xiaomeng; Harris, Robin E.; Bayston, Laura J.; Ashe, Hilary L. (Nature, 2008)
Dorsal–ventral patterning in vertebrate and invertebrate embryos is mediated by a conserved system of secreted proteins that establishes a bone morphogenetic protein (BMP) gradient. Although the Drosophila embryonic Decapentaplegic (Dpp) gradient has served as a model to understand how morphogen gradients are established, no role for the extracellular matrix has been previously described. Here we show that type IV collagen extracellular matrix proteins bind Dpp and regulate its signalling in both the Drosophila embryo and ovary. We provide evidence that the interaction between Dpp and type IV collagen augments Dpp signalling in the embryo by promoting gradient formation, yet it restricts the signalling range in the ovary through sequestration of the Dpp ligand. Together, these results identify a critical function of type IV collagens in modulating Dpp in the extracellular space during Drosophila development. On the basis of our findings that human type IV collagen binds BMP4, we predict that this role of type IV collagens will be conserved. Dorsal–ventral patterning: collagens and BMP signalling In both vertebrate and invertebrate embryos dorsal-ventral patterning is controlled by a concentration gradient of secreted signalling molecules called BMPs or bone morphogenetic proteins. Work in Drosophila now shows the extracellular matrix pays a part in regulating the Dpp morphogen gradient (Dpp is the Drosophila form of BMP). Type IV collagen binds to the Dpp ligand and regulates its signalling in the Drosophila embryo and ovary by sequestering Dpp. Human type IV collagen binds the analogous protein in humans, BMP-4, suggesting that this role of type IV collagens is widely conserved. This paper establishes a role of the extracellular matrix for regulating the BMP morphogen gradient responsible for dorsal–ventral patterning of vertebrate and invertebrate embryos. Type IV collagen binds to the Dpp ligand (the Drosophila form of BMP) and regulates its signalling in the Drosophila embryo and ovary by sequestering Dpp. Human type IV collagen binds the analogous protein in humans.